Environmental mechanism of capturing nutrient-rich particles by the lake bottom trap in a large, shallow lake. (November 2022) - Zhang, Yihui; Hu, Yuemin; Peng, Zhaoliang; Hu, Weiping; Zhu, Jinge
Abstract: Bottom traps capture and preserve nutrient-rich mobile bottom sediments by forming a weak hydrodynamic environment. In this study, Lake Chaohu, a large shallow lake in China, was considered the research object, and the influence of trap at the bottom of the lake on the physical, chemical, and biological characteristics of sediments and water were analysed by combining on-site monitoring and laboratory analysis. The results showed that the hydrodynamic intensity was attenuated by more than 65% at the bottom of the trap compared with that of the upper surface of the water body under different weather conditions, forming an obviously weak hydrodynamic environment. The weak dynamic environment and large sedimentation rate at the bottom of the trap were beneficial to the sedimentation and storage of fine particles that adsorb nutrients, such as nitrogen and phosphorus, in the water. Owing to the increase in local water depth, a low-temperature and low-dissolved oxygen environment was formed inside the trap. The abundance and diversity of microorganisms in the sediments inside the trap were reduced, and the abundance of nitrifying and denitrifying bacteria in the sediment was reduced by approximately 50%, indicating an environment favourable for nitrogen accumulation in the sediment in the trap. Therefore, the environment inside the bottom trap is favourable for capturing the high nutrient-rich particulate matter in the water, which provides theoretical support for use of the lake bottom traps for controlling the endogenous pollution of shallow lakes. Graphical abstract: Image 1 Highlights: Environmental characteristics inside the trap changed significantly. Weak hydrodynamic state was formed inside the bottom trap. The sediments inside the trap comprised dominant fine particles rich in nutrients. Abundance and diversity of bacterium in the sediments inside the trap decreased.